Analysis of Confidence Levels of Rich Slalom Rowing Athletes Hours - Rhama Nurwansyah Sumarsono (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study was to assess the level of confidence of athletes such as fast current slalom. This study uses the ex-post facto methodology. Purposive sampling was used to select 12 athletes consisting of 7 males and 5 females. The questionnaire used for data collection was given to rowing athletes such as heavy current slaloms. The self-confidence instrument is a method used to collect research data. The result is, of the 5 male athletes, the "high" group experienced the greatest growth, or 71%, and of the 5 female athletes, the "medium" category experienced the largest increase, or 100%. A lower percentage of the high category can be found in the very high category. This shows that both male and female athletes have a high level of confidence when competing, according to the data collected from the questionnaire. not too high and not too low. As a result, these athletes still have a reasonable level of confidence when competing.